Comparative Management Analysis Knowledge in Colombian and Chilean SMEs: Theoretical Approach (2022)
The objective of this study is to develop a comparative study of knowledge management and the most representative models applied in Chilean SMEs versus the models proposed in Colombia, with the purpose of adopting those good practices that allow more SMEs in Colombia to improve performance in the areas of the organization and optimize the transfer of their knowledge to obtain a competitive advantage. © 2022 Latin American and Caribbean Consortium of Engineering Institutions. All rights reserved.